Rancang Cipta Lagu Anak-Anak Berbasis Karakter Nilai Kesantunan - Kurniawati Kurniawati; Yona Wahyuningsih; Uus Uus Kusnadi (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2019)
The phenomenon of children's song crises, especially those based on the values of politeness, is an important issue that must be addressed wisely. Children's songs are rarely taught at school because children feel bored with the songs that have been delivered when in kindergarten. This causes children to tend to prefer adult songs which, of course, are inadequate for the mental maturity conditions of children. Adult songs, whether they are pop, rock, metal, or dangdut lack the modesty characters needed by children because they are not consumed by children. Charity value characters have not been optimized such as greeting, excuse me, please, apologize, and thank you. This problem is a challenge in the design and creation of children's songs based on politeness values. Song copyright design has stages of identification, design, manufacture, recording, and feasibility testing. The song creation is expected to be one of the modification of the results of the theme of politeness and make it a habit of modesty.